Application of treated eggplant peel as a low-cost adsorbent for water treatment toward elimination of Pb: Kinetic modeling and isotherm study - Mohammad Hossein Karimi Darvanjooghi; Seyyed Mohammadreza Davoodi; Arzu Y Dursun; Mohammad Reza Ehsani; Iman Karimpour; Elham Ameri (Adsorption Science & Technology)
In this study, treated eggplant peel was used as an adsorbent to remove Pb 2+ from aqueous solution. For this purpose batch adsorption experiments were performed for investigating the effect of contact time, pH, adsorbent dose, solute concentrations, and temperature. In order to assess adsorbent’s physical and chemical properties, Fourier transform infrared spectroscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy were used. The results showed that the adsorption parameters for reaching maximum removal were found to be contact time of 110 min, adsorbent dose of 0.01 g/ml, initial lead(II) concentration of 70 ppm, pH of 4, and temperature of 25°C. Moreover, for the experiments carried out at pH > 4 the removal occurred by means of significant precipitation as well as adsorption. Furthermore, these results indicated that the adsorption followed pseudo-second-order kinetics model implying that during the adsorption process strong bond between lead(II) and chemical functional groups of adsorbent surface took place. The process was described by Langmuir model (R 2  = 0.99; maximum adsorption capacity 88.33 mg/g). Also thermodynamics of adsorption was studied at various temperatures and the thermodynamic parameters including equilibrium constant (K), standard enthalpy change, standard entropy change, and standard free energy changes were obtained from experimental data.